From silence to curiosity: outdoor science learning and students’ courage to ask questions in rural communities - Maria Senisum; Wahyuni Purnami; Rizkia Suciati; Siti Nor Amira Bt Baharudin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Students residing in rural communities require conducive learning environments to cultivate the courage to ask questions in the learning process. The act of posing inquiries signifies the capacity to transcend a conventional and rigid learning environment. This research objective is to determine whether outdoor learning methodologies increase students' willingness to ask questions in science learning in rural communities. This quantitative descriptive study examined 51 elementary students residing in rural communities. Data on students' question-asking skills were collected through five distinct items. The data were collected using two techniques: observation and interviews. The results indicated that 61.3% of students demonstrated the ability to formulate questions spontaneously, 52.1% exhibited a capacity to respond to their peers' inquiries, 39.5% exhibited confidence when posing questions, 33.1% of questions were pertinent to the context of the material, and 32.5% of students employed standard Indonesian in their questioning. The utilisation of outdoor learning methodologies in scientific education can address students' tendency in rural communities to be reticent about seeking knowledge. However, developing an outdoor learning design that provides enhanced support for these students is imperative to foster their confidence in asking questions and to prevent bullying.